Thematic analysis in najat khayyat’s satashriqu al-shamsu yawma “one day the sun will rise” (2015)
Writers such as Najat Khayyat present the status of women not as passive but as women who experience psychological retrieval and decide to reform themselves. Here, I try to analyse her story satashriqu al-shamsu yawma (One day The Sun will Rise) which was published in the year 2001 in mawsucat al-adab al-arabial- sucudi al-hadith. Her writing, in this story, skillfully operates on simple classical Arabic language, al-fushd. It is an enjoyable literary text, written in smooth, fluent and captivating manner. It poses questions about women’s freedom, hope and optimism.